Implementation of Efforts to Control Homosexual Deviance at Sukadana Class IIB Detention Center - Pedro Richardo; Budi Priyatmono; Edo Prihantoro (Penerbit Hellow Pustaka, 2025)
Homosexuality itself is not something new; in fact, it has existed as a societal phenomenon in the past, such as in the cities of Sodom, Amurah, Adma', Sabubim, and Bala'. In this article, we will only discuss the effectiveness of controlling homosexual deviations in Rutan (Detention Center) Class IIB Sukadana. Using qualitative methodology, particularly by studying various literature as analytical material and addressing the issues through narrative form, the research findings indicate that deviant behavior can occur anywhere, both within families and in society. The tendency towards such behavior is influenced by individual personality factors, primarily biological factors such as genetic influences in shaping such personalities. Meanwhile, social heredity is mostly influenced by incorrect forms of socialization. The supportive factors for community leaders in preventing LGBT (Lesbian, Gay, Bisexual, and Transgender) behavior include community participation in combating LGBT behavior and support from the government and religious and formal educational institutions. On the other hand, there are factors that hinder the efforts to minimize LGBT behavior.